2017
DOI: 10.2217/bmm-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of MIRNA-Autophagy Transcript Expression in Patients With Hepatocellular Carcinoma

Abstract: The current work provides four RNA-based biomarker panel for HCC diagnosis and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Many studies have demonstrated dysregulated expression of specific miRNA in hepatocellular carcinoma patients . Moreover, miRNAs constitute a large gene regulatory network that plays important roles in various developmental and physiological processes, including cancer.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have demonstrated dysregulated expression of specific miRNA in hepatocellular carcinoma patients . Moreover, miRNAs constitute a large gene regulatory network that plays important roles in various developmental and physiological processes, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated dysregulated expression of specific miRNA in hepatocellular carcinoma patients (2).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations